1978
DOI: 10.1530/jrf.0.0540405
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vasectomy on the testes of inbred Lewis rats

Abstract: Summary. By 3 months after surgery, testicular weights were 12\p=n-\14% below control values in a large series of vasectomized rats of the inbred Lewis strain. Testicular sperm concentrations in the vasectomized rats were 25\p=n-\29 % below those in the sham-operated animals. Although modest in magnitude, these differences were highly significant (P < 0\m=.\001).Histometric analysis of testes from a smaller series of vasectomized Lewis rats revealed various proportions of abnormal seminiferous tubules. The deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

1980
1980
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…If penetration of aged testicular tubules by lanthanum is a physiologically significant indication of a defective blood-testis barrier, the arrested development of spermatogonia and spermatocytes may be the result of an altered intra-tubular microenvironment. Consistent with this view, Neaves (1978) found lanthanum-permeable 'tight' junctions with reduced sperm production in the testes of vasectomized Lewis rats. However, further explanations of sperm cell attrition must be sought because the integrity of the blood-testis barrier was apparently maintained in the majority of atrophie tubule segments.…”
Section: Discussionsupporting
confidence: 68%
“…If penetration of aged testicular tubules by lanthanum is a physiologically significant indication of a defective blood-testis barrier, the arrested development of spermatogonia and spermatocytes may be the result of an altered intra-tubular microenvironment. Consistent with this view, Neaves (1978) found lanthanum-permeable 'tight' junctions with reduced sperm production in the testes of vasectomized Lewis rats. However, further explanations of sperm cell attrition must be sought because the integrity of the blood-testis barrier was apparently maintained in the majority of atrophie tubule segments.…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to the severe testicular alterations observed in both adult and developing rats with epididymal or efferent duct ligations, changes after vasectomy have been more variable. Lewis rats developed testicular lesions consisting of depletion of germ cells and fusion of spermatids after adult vasectomy (Neaves, 1978;Flickinger et al, 1987;Herr et al, 1987;Chehval et al, 1995), but prepubertal obstruction of the vas deferens did not result in testicular changes (Flickinger et al, 1995), and testicular alterations are less frequent following adult vasectomy in Sprague-Dawley or Wistar strains of rats (Smith, 1962;Flickinger, 1972).…”
Section: Discussionmentioning
confidence: 91%
“…Multinucleated giant cells are common in vasectomy-induced spermatogenic damage, probably as a result of germ cell sloughing, an increase of pressure in the seminiferous tubules and an autoimmune reaction [37,47,51]. A histophysiological study of vasectomized rats indicated that a higher frequency of stage Ⅶ-Ⅷ of the tubular cycle was observed, showing sperm accumulation [25].…”
Section: Discussionmentioning
confidence: 99%